2015
DOI: 10.1097/cin.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

The iPad

Abstract: This research explored the impact of tablet technology, in the form of Apple iPads, on undergraduate nursing and midwifery students' learning outcomes. In simulated clinical learning environments, first-year nursing students (n = 30) accessed apps and reference materials on iPads. Third-year nursing students (n = 88) referred to clinical guidelines to aid their decision making when problem solving. First-year midwifery students (n = 25) filmed themselves undertaking a skill and then immediately played back the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The students also used the handheld device to answer patient questions promptly about their medication [28]. In a study of nursing students' experience with the PDA in a clinical setting, Johansson et al found that nearly half of the students used the PDA at the patient bedside.…”
Section: Nursing Students' Use Of Mobile Devicesmentioning
confidence: 99%
See 4 more Smart Citations
“…The students also used the handheld device to answer patient questions promptly about their medication [28]. In a study of nursing students' experience with the PDA in a clinical setting, Johansson et al found that nearly half of the students used the PDA at the patient bedside.…”
Section: Nursing Students' Use Of Mobile Devicesmentioning
confidence: 99%
“…Furthermore, there was a concern with text entry on mobile devices [24,26,34,37] using a virtual keyboard [25] and the small size screen inherent in tablet computers [34[. Another major concern was the cost associated with ownership of mobile devices [16,26,28,[30][31][32]40] and subscription to mobile applications [16,22,37,40]. Subscriptions to mobile applications, particularly subject content resources, imposed an additional burden to students, not to mention the financial cost incurred for renewing subscriptions.…”
Section: Benefits Of and Challenges In Accessing Resources On Mobile mentioning
confidence: 99%
See 3 more Smart Citations